Pengembangan Media Pembelajaran Game Edukasi Kolopoli Berbasis Android Pada Materi Sistem Koloid - Mega Yulia Devi; Ratna Sari Siti Aisyah; Imas Eva Wijayanti (Jurnal Pendidikan Kimia Undiksha, 2022)
The colloid system is a difficult material with the Minimum Completeness Criteria (KKM) value that is not exceeded at 92.41%. The tendency of memorized material to make students less active in the learning process. Educational games can be an effort to maximize the use of smartphones in education. This study aims to produce a product, determine the feasibility, and describe the student's response to the Android-based Kolopoly educational game learning media on the colloid system material. Development research with the ADDIE model used research subjects, namely 10 class XII students of SMAN 2 Rangkasbitung in the 2020/2021 school year. The results showed that Kolopoli was very feasible in the material sector with a percentage of 88.19% and the media sector with a percentage of 87.73%. Meanwhile, the results of student responses to the Kolopoli educational game as a learning medium got very feasible criteria with a percentage of 85.01%. Keywords: colloid system, educational games, Android, learning media, ADDIE